Body art - Brown, Brian; Kuulei Berndt, Virginia (Arts for health., 2023)
Body art, especially tattoos and piercings, has enjoyed an explosion of interest in recent years. However, the response of many health professionals and researchers to this phenomenon is often negative, as body art continues to be associated with issues ranging from ill mental health to offending behaviors. Arguing for a reappraisal of the diverse range of practices that fall under this heading, Brian Brown and Virginia Kuulei Berndt reconsider body art as an underappreciated yet accessible source for mental and physical wellbeing. How, they ask, does body art open up new sources of community, sociality, and aesthetics? How is it used for the reclamation of one's body, as a marker of success or accomplishment, or for building friendships? How does participation in these practices impact the health and wellbeing of body artists themselves? Providing a radical rethink that integrates tattoos and other body modifications within health, wellbeing, and positive psychology, Body Art disrupts the narrative of stigmatisation that so often surrounds these practices to welcome a broader discussion of the benefits they can offer.